Developing a Core Model for Expected Characteristics of Group Exercise Instructors in Sports Science Students - Yanyong Phanpheng; Pattarapol Thongnum; I Dewa Made Aryananda Wijaya Kusuma; Nur Azis Rohmansyah; Austtasit Chainarong; Kawin Boonprakorn (OVS LLC, 2024)
Background. Sports science experts play a crucial role in providing insights and appropriatere commendations to delineate the desired traits of professional group exercise instructors. Objectives. The study aimed to investigate the using expert Delphi techniques in developing a core model for expected characteristics of group exercise instructors in sports science students. Materials and methods. The study involved 18 exercise experts who served as group exercise instructors and lecturers in sports science. Across three questionnaire rounds, the data was assessed using a rating scale, considering Mode (Mo), Median (Mdn), and Interquartile range (IQR). Results. The experts consistently emphasized the development of the eight core characteristics of group exercise at the highest importance level (Mo = 5, Mdn = 5, IQR = 0). Their focus encompassed areas such as knowledge in anatomy and exercise physiology, proficiency in exercise techniques, understanding of movement, psychological aspects, the role of aerobic dance leadership, and attitude towards group exercise. Additionally, knowledge related to injury prevention and nutrition received respective scores of Mo = 4, Mdn = 4, IQR = 1. Being a group exercise instructor necessitated both physical and mental preparedness. Conclusions. The desired characteristics for sports science students who will develop themselves to be group exercise leaders have to include a broad range of knowledge to become a personality model, proficiency in all 8 areas, and the ability to effectively teach that lead students to success. And most importantly, the FITT-VS (Frequency Intensity Training Time Training Type-Volume Progression) principles of teaching should be applied in organizing the group exercise program to ensure appropriateness for each format.